A reversed-phase compatible thin-layer chromatography autography for the detection of acetylcholinesterase inhibitors - Ramallo, Ivana Ayelen (2015)
A dual readout autographic assay to detect acetylcholinesterase inhibitors present in complex matrices adsorbed on reversed-phase or normal-phase thin-layer chromatography plates is described. Enzyme gel entrapment with an amphiphilic copolymer was used for assay development. The effects of substrate and enzyme concentrations, pH, incubation time, and incubation temperature on the sensitivity and the detection limit of the assay were evaluated. Experimental design and response surface methodology were used to optimize conditions with a minimum number of experiments. The assay allowed the detection of 0.01% w/w of physostigmine in both a spiked Sonchus oleraceus L. extract chromatographed on normal phase and a spiked Pimenta racemosa (Mill.) J.W. Moore leaf essential oil chromatographed on reversed phase. Finally, the reversed-phase thin-layer chromatography assay was applied to reveal the presence of an inhibitor in the Cymbopogon citratus (DC.) Stapf essential oil. The developed assay is able to detect acetylcholinesterase inhibitors present in complex matrixes that were chromatographed in normal phase or reversed-phase thin-layer chromatography. The detection limit for physostigmine on both normal and reversed phase was of 1×10-4 μg. The results can be read by a change in color and/or a change in fluorescence.